Policy recommendations to enhance nursing education and services among Asean member countries - Koy, Virya (International Journal of Advances in Medicine, 2017)
The initiated the development of an ASEAN Community in 1967, the process will be complete in 2015. An ASEAN community comprises the ASEAN Economic Community (AEC), which has a single market and a production base which is stable, prosperous, highly competitive and with a free flow of goods or services and capitals. All services in ASEAN countries must be prepared for the coming changes. As a leader in the provision of health services of ASEAN countries will benefit most from joining this community. Nursing is an important profession in providing health care services. Therefore nursing schools, which have a major role in producing professional nurses, must prepare nursing staff to be involved in the ASEAN community. They must be able to know related information, for instance the collaborative memorandum of understanding among the ASEAN nursing profession for being the competitively advantaged organization. The exchanging of nursing knowledge and nursing service experience from ten ASEAN countries, establish each other county’s viewpoint of this knowledge. Furthermore, from the basis procedure of each country, we can move forward together to strengthen nursing education and nursing service in ASEAN countries and the world.